2005
DOI: 10.1002/art.20792
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone, a peroxisome proliferator–activated receptor γ agonist, reduces the progression of experimental osteoarthritis in guinea pigs

Abstract: Objective. To evaluate the in vivo therapeutic effect of pioglitazone, a peroxisome proliferatoractivated receptor ␥ (PPAR␥) agonist, on the development of lesions in a guinea pig model of osteoarthritis (OA), and to determine the influence of pioglitazone on the synthesis of matrix metalloproteinase 13 (MMP-13) and interleukin-1␤ (IL-1␤) in articular cartilage.Methods. The OA model was created by partial medial meniscectomy of the right knee joint. The guinea pigs were divided into 4 treatment groups: unopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
102
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 41 publications
9
102
0
1
Order By: Relevance
“…This effect was mainly related to a reduction in the severity of structural changes and loss of matrix aggrecans, as shown by the protective effect of the drug on the loss of Safranin O staining. These findings are again consistent with those by Kobayashi et al (19) in the guinea pig model, and suggest that pioglitazone treatment has significant positive effects on major OA cartilage catabolic processes.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This effect was mainly related to a reduction in the severity of structural changes and loss of matrix aggrecans, as shown by the protective effect of the drug on the loss of Safranin O staining. These findings are again consistent with those by Kobayashi et al (19) in the guinea pig model, and suggest that pioglitazone treatment has significant positive effects on major OA cartilage catabolic processes.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, pioglitazone was found to preferentially reduce the development of cartilage lesions on the femoral condyles. These findings are very much in accordance with those previously reported in a study in which pioglitazone was used as treatment in a guinea pig model of medial meniscectomy-induced OA (19). In the latter model, the protective effects of the drug were noted on the medial tibial plateaus, which is to be expected, since the lesions are preferentially distributed at that anatomic site in the guinea pig model.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…There is also some evidence to suggest that PPARG2 activation may be chondroprotective by negatively regulating the expression of matrix metalloproteinase-1 and matrix metalloproteinase-13 and by preventing proteoglycan degradation 4589. It has also been shown that treatment with a PPARG2 activator, pioglitazone, shows beneficial effects in an experimental model of OA 10. Therefore, it has been postulated that PPARG2 could be a candidate gene for susceptibility to OA.…”
mentioning
confidence: 99%